Documentação de acervos museológicos: um estudo de caso do acervo de vestuário do estilista André Lima na seção moda da Coleção Amazoniana de arte da UFPA - SANTOS, Sammya Daniele Paixão dos (2019)
The present work has the objective to search throught a case study based on the documentation actions of museological collections carried out without the collection of clothing by the stylist André Lima of the Fashion Section of the Amazonian Collection of Art of UFPA. Based on these initial actions that were developed without an extension project " Ações de Curadoria de Acervo na Seção Moda da Coleção Amazoniana de Arte " consisted, first, of a list that aims at quantification and qualification of the pieces and their materials, being possible a creation of a Classification plan for the clothing stock; As well as identifying the general terms for vocabulary control, given that it is a fashionable collection and these objects are not always easy to identify. Thus, after a classification of the pieces were created with specific metadata for this collection in the catalog.